The Effects of Shading Regimes on the Growth of Cocoa Seedlings(Theobroma cacao L.) - Raja Harun, Raja Muhammad; Ismail, Kamariah (Universiti Putra Malaysia Press, 1983)
An experiment was conducted to study the effects of different shading regimes: 80, 55, 30 and a percent i.e. full sunlight on the growth of cocoa seedlings during the first five months in the nursery. It was observed that the shading regime for optimal dryweight accumulation was under 80 percent shade during the first three months gradually reducing to 55 percent shade from the fourth month onwards. This interaction between age and shading regime was brought about by changes in net assimilation rates in response to self shading as the plant aged and also to the effects of lead production in response to different light intensities. Totally unshaded condition was detrimental to plant growth. Shading practice has to take into account the balance between capacity for leaf production and optimal capacity for assimilation.